2011
DOI: 10.2753/ree1540-496x470302
|View full text |Cite
|
Sign up to set email alerts
|

Start-Up Financing in the Age of Globalization

Abstract: The authors investigate the determinants of start-up financing in fifty-four countries, using the Global Entrepreneurship Monitor (GEM) surveys for the years 2001-6. They find that financial liberalization increases the total financial size of the individual start-up entrepreneurial project both via the increased use of external and of own funds. In addition, the volume of start-up finance responds positively to international capital inflows, as represented by loans from nonresident banks and remittances, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 45 publications
0
34
0
3
Order By: Relevance
“…Young or established entrepreneurs are those whose business has paid salaries, wages or in kind for three months or longer and they own and manage that business. Past research points to the importance of access to capital for potential entrepreneurs who engage in the start-up process, both commercial (e.g., Ho and Wong, 2007;Korosteleva and Mickiewicz, 2011) and social (Meyskens et al, 2010). It has also been identified as critical to include alongside human capital variables, as the two forms of capital are correlated, and otherwise an omitted variable bias could result.…”
Section: Individual-level Control Variablesmentioning
confidence: 99%
“…Young or established entrepreneurs are those whose business has paid salaries, wages or in kind for three months or longer and they own and manage that business. Past research points to the importance of access to capital for potential entrepreneurs who engage in the start-up process, both commercial (e.g., Ho and Wong, 2007;Korosteleva and Mickiewicz, 2011) and social (Meyskens et al, 2010). It has also been identified as critical to include alongside human capital variables, as the two forms of capital are correlated, and otherwise an omitted variable bias could result.…”
Section: Individual-level Control Variablesmentioning
confidence: 99%
“…Better developed financial institutions, to the extent of mitigating external finance constraints, are found to disproportionally benefit smaller firms (BECK et al, 2005). With wider supply of finance and competition, the financial institutions are pushed to choose more risky financial options including entrepreneurial finance (KOROSTELEVA and MICKIEWICZ, 2011). This is particularly topical for transition economies, for which scarcity of financial resources is documented as one of the major obstacles for entrepreneurship development (PISSARIDES et al, 2003).…”
Section: Control Variablesmentioning
confidence: 99%
“…It has been recognised that individuals often use personal income and wealth as a source of start-up capital (Fraser 2004;Gartner et al 2004;Rouse and Jayawarna 2006;Korosteleva and Mickiewicz, 2011). Consistent with this, studies have shown that financial capital is important in determining the probability of becoming an entrepreneur and of entrepreneurial success (see Black et al 1996;Blanchflower and Oswald 1998 for United Kingdom and; Evans and Leighton 1989;Evans and Jovanovic 1989;Holtz-Eakin et al 1994 for United States).…”
Section: Financial Capital As a Resource For Entrepreneurshipmentioning
confidence: 98%